The association of physical activity and cardiorespiratory fitness with β-cell dysfunction, insulin resistance, and diabetes among adults in north-western Tanzania: A cross-sectional study - Kitilya, Brenda; Peck, Robert; Changalucha, John; Jeremiah, Kidola; Kavishe, Bazil B.; Friis, Henrik; Filteau, Suzanne; Krogh-Madsen, Rikke; Brage, Soren; Faurholt-Jepsen, Daniel; Olsen, Mette F.; PrayGod, George (Frontiers in Endocrinology, 2022)
Introduction Research on the associations of physical activity and cardiorespiratory fitness with β-cell dysfunction and insulin resistance among adults in Sub-Saharan Africa is limited. We assessed the association of physical activity and cardiorespiratory fitness with β-cell function, insulin resistance and diabetes among people living with HIV ART-naïve and HIV-uninfected Tanzanian adults. Method In a cross-sectional study, we collected data on socio-demography, anthropometry, and C-reactive protein. Data on glucose and insulin collected during an oral glucose tolerance test were used to assess β-cell dysfunction (defined as insulinogenic index <0.71 (mU/L)/(mmol/L), HOMA-β index <38.3 (mU/L)/(mmol/L), and overall insulin release index <33.3 (mU/L)/(mmol/L)), insulin resistance (HOMA-IR index >1.9 (mU/L)/(mmol/L) and Matsuda index <7.2 (mU/L)/(mmol/L), prediabetes and diabetes which were the dependent variables. Physical activity energy expenditure (PAEE), sleeping heart rate (SHR), and maximum uptake of oxygen during exercise (VO2 max) were the independent variables and were assessed using a combined heart rate and accelerometer monitor. Logistic regressions were used to assess the associations. Results Of 391 participants, 272 were PLWH and 119 HIV-uninfected. The mean age was 39 (±10.5) years and 60% (n=235) were females. A 5 kj/kg/day increase in PAEE was associated with reduced risk of lower insulinogenic index (OR=0.94, 95%CI: 0.88, 1.01) and of higher HOMA-IR (OR=0.89, 95%CI: 0.83, 0.96), and with lower risk of pre-diabetes (RRR=0.88, 95%CI: 0.88, 0.94) and diabetes (RRR=0.65, 95%CI: 0.52, 0.82). An increment of 5 beats per min of SHR was associated with higher risk of diabetes (RRR=1.34, 95%CI: 1.08, 1.60). An increase of 5 mLO2/kg/min of VO2 max was associated with lower risk of pre-diabetes (OR=0.63, 95%CI: 0.48, 0.84), but not diabetes. HIV status did not modify any of these associations (interaction, p>0.05). Conclusion Among Tanzanian adults with and without HIV, habitual physical activity was associated with lower risk of β-cell dysfunction, insulin resistance and diabetes. Higher sleeping heart rate was associated with higher risk of diabetes, and VO2 max was associated with lower risk of pre-diabetes. Research is needed to assess if physical activity interventions can improve β-cell function and insulin sensitivity to reduce risk of diabetes and delay progression of diabetes in SSA.